Primary reconstruction with customized implants after resection of a large craniofacial tumor - Nuñez, José (2019)
We report the immediate reconstruction with personalized implants in the craniofacial region in a 22-year-old female patient with a craniofacial tumor of 12x15 cm in the left zygomatic orbital frontal region that corresponded to an ossifying fibroma. The reconstruction was performed with a custom-made implant based on tomographic images. The polyetheretherketone (PEEK) implant was selected to replace bone loss and restore facial anatomy. There was no need for transsurgical adjustment of the implant, no rejection, infection or implant exposure in the postoperative period. Although autologous bone is preferred for implants, it is often limited in the morbidity of the donor site, the difficulty of giving shape mainly to the borders and the limitation of the area to be donated; therefore the PEEK implants are currently an option in terms of biocompatibility resistance, duration, thermal conductivity and radiographic translucency.